NADI PARIKSHA: WRIST PULSE ANALYSIS WITH TRADITIONAL AND MODERN INTERPRETATION - Shashi, *Sharma; Neelam Rup, Prakash; Amod, Kumar (International Journal of Ayurveda and Pharma Research, 2017)
Nadi Pariksha (Pulse diagnosis) is considered the most important assessment in Traditional Medicine System (TMS) for health monitoring. Traditional pulse analysis is subjective and hard to quantify. It is difficult for a Ayurvedic doctor to understand the pulse by his own perception due to its arbitrariness. To realize due recognition of TMS, standard techniques and standard instruments are urgently to be developed. In view of the increasing popularity of traditional and alternative medicine worldwide, researchers have explored pulse sensing and analysis, but due to the conflict of research goals, methodologies and statistical tools applied, the outcome of studies till date is not focused in one direction. This study explores current status of pulse signal interpretation by researchers using latest electronic signal processing techniques in recent years. The aim of research is towards development of pulse sensing and analyzing techniques using latest technology to assist or help Ayurvedic doctors, in a way to promote our countrys traditional pulse sensing. Since no sensor is benchmarked as a standard in wrist pulse sensing till date, various sensors were explored to sense wrist pulse and the results were correlated with the recent research. Optical sensor HOA 709 in reflective mode, exhibited best results, it captured the minute details and was used to acquire pulse signal of healthy subjects at Pita point on radial artery. The sensor was explored further to record pre-meal and post-meal data of two subjects and significant variation in signal contour was noticed. It can further be explored to extract more parameters with the help of Ayurvedic doctors to make it useful in health care.